Verba Kompon Hajimeru, Dasu, Dan Kakeru Sebagai Penanda Aspek Inkoatif Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini (Diponegoro University, 2019)
(Title: Compound Verbs -Hajimeru, -Dasu, -Kakeru as An Inchoative Aspects Marker in Japanese Language) Compound verb -hajimeru, -dasu, and -kakeruare known as marker of inchoative aspects that express the beginning of a state. This study aims to describe the structure and meaning of the three compound verbs in order to be able to use the three markers of this aspect in the right situation. The method used in this research is descriptive method. As a result of the study it was found that the compound verb -hajimeru compound were used to express the beginning of an activity or event in general in Japanese; compound verb -dasu is used to express the beginning of an activity that occurs suddenly; while the compound verb -kakeru states that activity will begin in a moment, or states a moment after an activity begin .